Modeling Optimism with Positive affect Mediation: SEM Analysis in Surakarta Vocational Schools' Students - Aditya Nanda Priyatama; Sekar Ayu Jenar Mahesa; Dona Alloydya Shafira; Shofia Nur Izzati; Safira Nur A’yuni Damayanti (Indigenous: Jurnal Ilmiah Psikologi, 2025)
Abstract. Optimism is a positive expectation within individuals shaped by various internal and external factors. This study aims to examine the Optimism Model with positive affect as a mediator in the relationship between self-esteem, proactive personality, school connectedness, and parental attachment toward optimism among vocational high school students. The research was conducted quantitatively on 896 twelfth-grade students in Surakarta using simple random sampling. Data were collected using six standardized psychological scales: Rosenberg Self-Esteem Scale (RSES), Proactive Personality Scale (PPS), Measurement of School Connectedness (MOSC), Parental Attachment Scale, Life Orientation Test-Revised (LOT-R), and the Positive and Negative Affect Schedule (PANAS). Data analysis was carried out using Structural Equation Modeling (SEM) with Lisrel 9.10. The result indicate that the proposed model demonstrated good fit across several indices, supporting its structural validity. All four exogenous variables significantly influenced positive affect. However, positive affect did not significantly mediate optimism (t=0.53). optimism was more strongly influenced directly by self-esteem, proactive personality, and parental attachment. Although school connectedness showed no significant direct or indirect effects, its total contribution remained meaningful. These findings suggest that positive emotional experience is not the only pathway to optimism and highlight the direct role of psychosocial factors in fostering optimism among vocational students.Keywords: optimism; parental attachment; positive affect; proactive personality; school connectedness; self-esteem Abstrak. Optimisme merupakan ekspektasi positif pada individu yang dibentuk oleh berbagai faktor internal dan eksternal. Studi ini bertujuan menguji Model Optimisme dengan afek positif sebagai mediator dalam hubungan antara self-esteem, kepribadian proaktif, school connectedness, dan parental attachment terhadap optimisme siswa SMK. Penelitian dilakukan secara kuantitatif pada 896 siswa kelas XII di Surakarta dengan teknik simple random sampling. Instrumen pengumpulan data terdiri dari enam skala psikologis terstandar: Rosenberg Self-Esteem Scale (RSES), Proactive Personality Scale (PPS), Measurement of School Connectedness (MOSC), Skala Kelekatan Orang Tua, Life Orientation Test-Revised (LOT-R), dan Positive and Negative Affect Schedule (PANAS). Analisis data dilakukan dengan Structural Equation Modeling (SEM) menggunakan Lisrel 9.10. Hasil menunjukkan bahwa model optimisme yang diajukan fit dengan beberapa kriteria pendukungnya sehingga layak secara struktural untuk menjelaskan hubungan antar konstruk dalam model. Keempat variabel eksogen berpengaruh signifikan terhadap afek positif, tetapi afek positif kurang berperan sebagai mediator dalam pembentukan optimisme (t=0.53). Optimisme lebih dipengaruhi secara langsung oleh self-esteem, kepribadian proaktif, dan parental attachment. Sementara itu, school connectedness tetap memberikan kontribusi total yang bermakna meskipun tidak menunjukkan pengaruh signifikan secara langsung maupun tidak langsung. Temuan ini menegaskan bahwa pengalaman emosional positif bukan satu-satunya jalur pembentuk optimisme, serta pentingnya memperhatikan faktor-faktor psikososial yang bekerja secara langsung dalam mendukung optimisme siswa vokasional.Kata kunci: afek positif; kepribadian proaktif; optimisme; parental attachment; school connectedness; self-esteem